2015
DOI: 10.1086/682072
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Balance Modulates the Temperature-Size Rule in an Ectotherm

Abstract: Most ectotherms mature at a larger body size in colder conditions, a phenomenon known as the temperature-size rule. While a number of hypotheses have been proposed to explain this rule, little work has been done to understand it from a nutritional perspective. We have used the final-instar caterpillars of Spodoptera litura to investigate how dietary protein∶carbohydrate (P∶C) balance influences the relationship between temperature and body size. The strength and direction of the thermal reaction norm for body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 58 publications
5
73
1
Order By: Relevance
“…On the diets that produced the poorest trait outcomes, higher temperatures made these outcomes even worse. A similar interaction between temperature and diet was found in the caterpillar S. litura (Lee et al, ) which underwent a more acute decrease in size with carbohydrate‐rich food (1:5 P:C) when this diet was paired with higher temperatures, consistent with the current study.…”
Section: Discussionsupporting
confidence: 91%
“…On the diets that produced the poorest trait outcomes, higher temperatures made these outcomes even worse. A similar interaction between temperature and diet was found in the caterpillar S. litura (Lee et al, ) which underwent a more acute decrease in size with carbohydrate‐rich food (1:5 P:C) when this diet was paired with higher temperatures, consistent with the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that metabolic rates increase faster than consumption rates in many ectotherms with a temperature rise (Kingsolver & Woods, 1997) which may lead to mismatch between consumption and digestion in ectotherms (Lemoine & Burkepile, 2012). One potential strategy to reduce the mismatch is to consume a diet with more carbohydrates which can be easily utilized for energy (Lee et al, 2015). This would imply selection for a more carbon-based diet with increasing temperatures and, hence, more plants and less meat for omnivorous ectotherms (Boersma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrobiologia ( 2018) 812:147-155 151 carbohydrates at higher temperatures (Lee et al, 2015), whereas omnivorous fish consume proportionally more plant material with increasing temperatures (Prejs, 1984;Behrens & Lafferty, 2007Gonzá-lez-Bergonzoni et al, 2015). Similarly, the herbivorous amphipod Ampithoe longimana Smith, 1873, collected in a cold-temperate environment, consumed more low organic and protein content seaweeds at higher temperatures (Sotka & Giddens, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that omnivorous invertebrates increase the relative intake of plant over animal tissue at higher temperatures (Boersma et al., ; Carreira, Segurado, Laurila, & Rebelo, ; Carreira et al., ; Malzahn, Doerfler, & Boersma, ), presumably to obtain extra carbon to meet the increased metabolic costs for ectotherms at higher temperatures (Boersma et al., ). Studies using chemically defined diets specifically showed that mealworms ( Tenebrio molitor L.) (Rho & Lee, ) and Spodoptera litura caterpillars (Lee, Jang, Ravzanaadii, & Rho, ) increased their preference for carbohydrate relative to protein at higher temperatures. In contrast, rats kept in cold environments increased their absolute and proportional intake of carbohydrates relative to protein compared with warm environments (Simpson & Raubenheimer, ).…”
Section: Introductionmentioning
confidence: 99%